2021
DOI: 10.1021/acs.biomac.0c01746
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mesoscopic Morphology in Mussel Adhesive Proteins by Soft X-ray Spectromicroscopy

Abstract: Marine mussels efficiently adhere under wet conditions by precisely controlling the hierarchical structure of the adhesive plaque through sequential mussel foot protein secretion in the foot-tip cavity. Chemical analysis of the non-uniform mussel plaque morphology has been performed using spectromicroscopy; however, the mesoscopic morphology has not been elucidated yet because of the limited spatial resolution of conventional chemical imaging techniques. We investigated the chemical speciation in the non-unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As part of developing the analysis and evaluation, spectroscopic imaging techniques have been developed internationally in various fields, and as a pioneer, scanning transmission x-ray microscopy (STXM) applicable to the soft matter has been developed in UVSOR. To meet the recent demand for operand measurement, STXM is being further enhanced to apply to complex and heterogeneous systems [7][8][9][10][11][12][13][14][15]. In FY2020, we started the development of imaging for photoelectron spectroscopy.…”
Section: History Of Uvsormentioning
confidence: 99%
“…As part of developing the analysis and evaluation, spectroscopic imaging techniques have been developed internationally in various fields, and as a pioneer, scanning transmission x-ray microscopy (STXM) applicable to the soft matter has been developed in UVSOR. To meet the recent demand for operand measurement, STXM is being further enhanced to apply to complex and heterogeneous systems [7][8][9][10][11][12][13][14][15]. In FY2020, we started the development of imaging for photoelectron spectroscopy.…”
Section: History Of Uvsormentioning
confidence: 99%
“…Through modelling and molecular dynamics simulations, a disordered structure and elongated conformation is found for DOPA-rich Pvfp-5 proteins and DOPA moieties are on the protein surfaces. [29,63] By extracting and analysis of these mfps from natural mussels, it is found that the diversity of catechol chemistry plays a crucial role in maintaining its adhesion behaviour. [64]…”
Section: The Structure Of Mfpsmentioning
confidence: 99%
“…Interface-sensitive characterizations with high spatial resolution, providing multiscale structural information about adhesive molecules at the interface, are essential to verify the above-mentioned theories. Sum frequency generation (SFG) spectroscopy and soft X-ray absorption have shown that functional groups of adsorbed chains are oriented at the outermost surface of the adherends. Real-space observation, such as electron microscopy, has revealed the possibility of an interlocking or anchoring effect, , as described by the mechanical theory.…”
Section: Introductionmentioning
confidence: 99%